Modulation of surface plasmon coupled emission (SPCE) by a pulsed magnetic field1. Issue 61 (7th August 2015) - Xie, Kai-Xin; Cao, Shuo-Hui; Liu, Qian; Cai, Wei-Peng; Huo, Si-Xin; Watarai, Hitoshi; Li, Yao-Qun
<x xml:space="preserve">Abstract</x> The SPCE was modulated by a magnetic field through the interaction between plasmon and magnetic field.